2020
DOI: 10.14218/jcth.2020.00006
|View full text |Cite
|
Sign up to set email alerts
|

Hispanic Patients with Primary Biliary Cholangitis Have Decreased Access to Care Compared to Non-Hispanics

Abstract: Background and Aims: Hispanic patients with primary biliary cholangitis (PBC) have reduced rates of biochemical response to ursodeoxycholic acid (UDCA) and increased risk of disease progression compared to non-Hispanic patients. In this study, we sought to identify differences in demographics, comorbidities, environmental risk factors and socioeconomic status between Hispanic and non-Hispanic patients with PBC. Methods: In a case control study, we analyzed data from Hispanic (n=37 females and 1 male) and non-H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…(9) A case-control study from the same group reported lower income, decreased education level, and less insurance coverage in the Latinx cohort. (19) While there may be a genetic predisposition to severe disease and variant syndromes in Latinx patients, this study highlights the importance of considering the contribution of nonbiological factors such as medication adherence, health literacy, and access to health care in the observed disparities.…”
Section: Primary Biliary Cholangitismentioning
confidence: 83%
See 1 more Smart Citation
“…(9) A case-control study from the same group reported lower income, decreased education level, and less insurance coverage in the Latinx cohort. (19) While there may be a genetic predisposition to severe disease and variant syndromes in Latinx patients, this study highlights the importance of considering the contribution of nonbiological factors such as medication adherence, health literacy, and access to health care in the observed disparities.…”
Section: Primary Biliary Cholangitismentioning
confidence: 83%
“…A summary of recommendations for the hepatology community is provided in Table 3. • Increased complications of liver disease in Latinx PBC hospitalizations (n = 1,430) (14) • Increased waitlist mortality for Latinx patients with PBC (n = 793) (25) • Latinx patients with AIH present with more severe disease, including cirrhosis (n = 20, n = 58) (46,50) • Latinx patients have a higher prevalence of PNPLA3 polymorphism (n = 327) (52) ; a certain PNPLA3 variant in AIH was identified to be predictive of LT or death (54) No data available Black • Prevalence of PBC in Blacks is greater than previously reported and Black patients with PBC are less likely to get treated with UDCA (n = 286) (17) • Increased mortality compared to White patients with PBC (n = 390) (16) • UDCA in Black patients with PBC can reverse mortality risk (n = 339) (18) • Black patients with AIH present younger and have more cirrhosis on presentation (n = 27) (40) • Black patients with AIH had higher rates of death or LT (n = 37) (39) • Black patients with AIH have a higher rate of LT and death, despite similar rates of response and relapse (n = 88) (42) • Prevalence of PSC in Black patients may be greater than previously reported (n = 193) (59) • Black patients with PSC and IBD had greater risk of LT or PSC-related death compared to White patients with PSC (n = 65) (61) Asian/AAPI, AI/AN • Prevalence of PBC in Asians is underreported (27) • Prevalence of PBC is even greater in Asian Americans (n = 252) (17) • Asian Americans with untreated PBC have a higher risk of death or LT compared to White patients (n = 297) (18) • Asian Americans with AIH had poorer survival outcomes (n = 17) (46) No data available (24) cadmium, (24) environmental factors, (22,76) antidepressants (77) Urban, industrial, coal (24) Insurance status of Latinx patients (19) Organ allocation (78) Smoking (79,80) Latinx (19) , transplant availability…”
Section: Discussionmentioning
confidence: 99%
“…Caution should be exercised when generalising our findings to the wider PBC population, especially in different countries and varying healthcare systems. Additionally, potential differences in clinical practice and socioeconomic discrepancies, such as access to care, should also be considered 33 34. Collectively, these limitations highlight that there is a clear need for high quality data, including from both structured and unstructured databases as well as patient-reported outcome data to fully address the burden of PBC and associated pruritus in real-world practice.…”
Section: Discussionmentioning
confidence: 99%
“…Not all patients benefit from UDCA treatment to the same degree, with several studies showing variable responses to the medication according to age, race, and histological stage at diagnosis. 67 , 68 Younger age, advanced fibrosis (stage 3/4) at the time of treatment initiation, and male sex are associated with poor biochemical response to UDCA. 59 , 69 Hispanic patients are more likely to exhibit features of autoimmune hepatitis and to have higher rates of biochemical nonresponse.…”
Section: Prognosismentioning
confidence: 99%